Analysis Motivation to Start A Start-Up Business Start-Up to The Youth of Romania - David-Florin CIOCODEICA (Communications of International Proceedings, 2020)
One of the main aims of European policies in the new knowledge-based society is to make the economy in the European space the most competitive and dynamic, capable of sustainable growth, with more and better jobs, with greater social cohesion. In order to achieve this objective, the competitiveness of the organizations must continuously improve, in the conditions of a labour market that will adapt quickly to the changes in the economic, social and informational environment and to the modernization of the work process based on higher qualifications, efficiently capitalizing on the well-prepared human resources from a professional point of view. The purpose of this paper is to bring a surplus of value by presenting the most important information about entrepreneurship in Romania, starting with the conceptual delimitations of entrepreneurship and entrepreneur, and continuing with the sector of small and medium-sized enterprises, management, managerial functions, creation and development of the start-up sector and specific strategies for start-ups. It also brings to mind the motivation of young people to start their own business and to have the most efficient and accurate information when they decide to set up an organization / enterprise, as well as how the entrepreneurial principles can be applied in any area and area, in every action carried out in daily activities.
Keywords: Entrepreneurship; Entrepreneurial Marketing; Start-Ups; Campaign; Economic.